In Situ and Orbital Stratigraphic Characterization of the InSight Landing Site—A Type Example of a Regolith‐Covered Lava Plain on Mars. Issue 4 (26th April 2022) - Warner, N. H.; Golombek, M. P.; Ansan, V.; Marteau, E.; Williams, N.; Grant, J. A.; Hauber, E.; Weitz, C.; Wilson, S.; Piqueux, S.; Mueller, N.; Grott, M.; et al.
Abstract: The InSight lander rests on a regolith‐covered, Hesperian to Early Amazonian lava plain in Elysium Planitia within a ∼27‐m‐diameter, degraded impact crater called Homestead hollow . The km to cm‐scale stratigraphy beneath the lander is relevant to the mission's geophysical investigations. Geologic mapping and crater statistics indicate that ∼170 m of mostly Hesperian to Early Amazonian basaltic lavas are underlain by Noachian to Early Hesperian (∼3.6 Ga) materials of possible sedimentary origin. Up to ∼140 m of this volcanic resurfacing occurred in the Early Amazonian at 1.7 Ga, accounting for removal of craters ≤700 m in diameter. Seismic data however, suggest a clastic horizon that interrupts the volcanic sequence between depths of ∼30 and ∼75 m. Meter‐scale stratigraphy beneath the lander is constrained by local and regional regolith thickness estimates that indicate up to 10–30 m of coarse‐grained, brecciated regolith that fines upwards to a ∼3 m thick loosely‐consolidated, sand‐dominated unit. The maximum depth of Homestead hollow, at ∼3 m, indicates that the crater is entirely embedded in regolith. The hollow is filled by sand‐size eolian sediments, with contributions from sand to cobble‐size slope debris, and sand to cobble‐size ejecta. Lander‐based observations indicate that the fill at Homestead hollow contains a cohesive layer down to ∼10–20 cm depth that is visible in lander rocket‐excavated pits and the HP 3 mole hole. The surface of the landing site is capped by a ∼1 to 2 cm‐thick loosely granular, sand‐sized layer with a microns‐thick surficial dust horizon. Plain Language Summary: The InSight lander has geophysical instruments that are designed to determine the interior structure of Mars. Understanding the results from these instruments requires a geological analysis of materials beneath the landing site at Elysium Planitia. This study presents data that describe the vertical sequence of rocks and soils beneath the lander, as well as the geologic history. The results indicate that InSight rests on a 1.7‐billion‐year‐old lava plain that is covered in a 10–30 m thick regolith that was produced by impact cratering and modified by wind. The uppermost portion of the regolith is a ∼3 m thick horizon of sand. InSight rests on sand within a degraded impact crater. The sandy material contains a slightly cohesive horizon that is only ∼1–2 cm beneath the lander and is up to 10–20 cm thick. The sandy horizon overlies rock fragments that get progressively larger with depth. Bedrock of basaltic lava exists beneath the regolith down to a depth of ∼170 m. The bedrock is interrupted by weaker materials between depths of ∼30 and 75 m. Beneath ∼170 m, the sequence is dominated by ancient (3.7–4.1 billion years old), possibly sedimentary materials. Key Points: InSight rests on Early Amazonian basaltic lava with an up to 10–30 m thick regolith. The upper 3 m of the regolith is sand dominated The regolith contains a 10–20 cm thick cohesive horizon or duricrust. This horizon rests 1–2 cm beneath the lander The upper 1–2 cm of the regolith comprises loosely‐consolidated sand to pebbles. Sand is rarely mobilized under current wind conditions